2001
DOI: 10.1007/s003300101070
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the foot and ankle: patterns of bone marrow signal abnormalities

Abstract: IntroductionMagnetic resonance imaging has demonstrated its usefulness in assessment of normal and abnormal bone marrow. Using MR imaging the continuous change of normal bone marrow composition throughout life and the varied responses of bone marrow to trauma or disease can be monitored [1].Magnetic resonance imaging characterization of location, morphology, distribution, and signal characteristics of a bone marrow abnormality enables diagnosis of a wide range of foot and ankle disorders with a high level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 27 publications
0
59
1
7
Order By: Relevance
“…The prevalence of changes in the current study is relatively high (50%). However, the extent and signal intensity of the bone marrow changes in the current study were substantially smaller than those in symptomatic patients with unexplained chronic foot pain, stress fractures, degenerative disorders, inflammatory arthropathies, necrosis, osteomyelitis, neuropathic arthropathy and other diseases [1,2,[4][5][6][7][8]13]. Admittedly, we have no quantitative comparison because previously published studies in symptomatic feet with bone marrow changes did not measure similarly in Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…The prevalence of changes in the current study is relatively high (50%). However, the extent and signal intensity of the bone marrow changes in the current study were substantially smaller than those in symptomatic patients with unexplained chronic foot pain, stress fractures, degenerative disorders, inflammatory arthropathies, necrosis, osteomyelitis, neuropathic arthropathy and other diseases [1,2,[4][5][6][7][8]13]. Admittedly, we have no quantitative comparison because previously published studies in symptomatic feet with bone marrow changes did not measure similarly in Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…Magnetic resonance imaging findings of stress fractures or stress injuries to bone are widely accepted [17,18,19]. In stress injuries to bone T1-weighted images show areas of low signal intensity, which on T2-weighted images or STIR images are of high signal intensity, these changes in MRI signal intensity represent edema of bone.…”
Section: Discussionmentioning
confidence: 98%
“…Weishaupt et al suggested that the double-line sign is more commonly seen in systemic disorders that have a predilection for the talus and calcaneus. 18 We have observed this sign in multiple cases of AVN of the distal tibia (►Fig. 3).…”
Section: Mrimentioning
confidence: 70%